Bio‐inspired functional coacervates: Special Issue: Emerging Investigators. Issue 6 (12th November 2022) - Chen, Shujun; Guo, Qi; Yu, Jing
Abstract: Many functional coacervates have been identified in biological systems, which have attracted widespread interest. Coacervation is a liquid–liquid phase separation (LLPS) process in which a macromolecule‐enriched liquid phase is formed together with a macromolecule‐depleted phase. Bio‐inspired coacervates possess excellent features such as underwater delivery, low interface energy, shear thinning, and excellent biocompatibility. They also serve as good delivery platforms for different types of molecules. In this review, we briefly discuss some important extracellular coacervate systems, including mussel adhesives, sandcastle worm glue, squid beak, and tropoelastin. We then provide an overview of the recent development of bio‐inspired functional coacervates for various biomedical applications, including medical adhesives, drug delivery, and tissue engineering. Bio‐inspired functional coacervates offer a promising material platform for developing new materials for biomedical applications. Abstract : Bio‐inspired functional coacervates have diverse functions. Natural and synthetic coacervates are a new class of materials that have great potential for various biomedical applications, including medical adhesives, drug delivery, and tissue engineering.